Cafe Coronary Syndrome-fatal Choking on Food: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
Cafe Coronary syndrome which was first reported as sudden collapse at restaurants while dining was found to be due to fatal occlusion of upper airway by large pieces of food. Many of those individuals had consumed large amounts of alcohol prior to the incident. Choking to death means asphyxiation by blockage of the internal air passages. If it occurs while eating, it is also called café coronary syndrome because it presents like an acute heart attack due to coronary obstruction. Sudden collapse during or shortly after a meal should always raise the possibility of café coronary and the autopsy examination should not only attempt to demonstrate airway occlusion by a bolus of food, but also to identify or exclude underlying neurological disease. A 27-year-old individual waiter had dinner in a restaurant after finishing his work. While eating a piece of meat, the man collapsed lifelessly. On internal examination, a piece of mutton bone was found in the larynx (3.5 x 1.4 cm) between the epiglottis and the vocal cords which was nearly complete obstruction of the larynx. The suppression of gag-reflex due to alcohol or drugs makes the individual susceptible to Cafe Coronary. This case highlights the need of being aware of the condition especially in the alcoholic/ intoxicated persons.
Keywords: Choking; Intoxication; Cafe coronary